O lazer como uma das possíveis estratégias de promoção da saúde nas classes subalternas: um estudo de caso na Zona Leste de São Paulo - Canton, Giselle Alice Martins (2008)
In the context of capitalist development, man is fragmented into his practices and is valued according to what he produces and consumes. The urban-industrial society imposes a life style where leisure opposes work and is dependant of a time that is free from work. The result is a mistaken idea that leisure is a manner to put up with the day-by-day activities, a way to restore energy. Thus, people lose the perspective of leisure as a privileged social practice which encompasses options, interests, postures and attitudes, something that raises the possibility of understanding it in an educational dimension. In this regard, it is justifiable to comprehend leisure, within this work, as a human experience that may contribute to the cultural development of social subjects, stressing their behaviour towards the health-illness process in order to promote good health. The conformation of the object of our research leisure as a strategy feasible to promote good health among subordinate classes - arouse from the notion of how leisure and health have been perceived as a social right in the everyday lives of these classes, whose subordinate identity is found in the lack of power of command, decision, creation, and direction. Working with analytic categories of health, leisure, and health promotion, we have recovered, from a historic-dialectic perspective, the trajectory taken by the perception of the health-illness process and the conceptual patterns that prevailed until the end of the 20th century, when the concept of promoting health got significance in Latin America. We have worked with the concept of leisure using the capitalism development period as a starting point, focusing on the importance of its educational dimension. Following the trajectory of cultural policies we have tried to find out how leisure has been dealt with. Our concern over dealing with the object of this research within a theoretical-practical dimension is exposed in this study by the chosen methodological course, which included a case study with subjects comprising users of a healthcare center in the east side of São Paulo city, Brazil. It is in this case study we have reflected on the issue of the research: what is the purpose of leisure in the daily routine of subordinate classes, with focus on promoting good health. Analyses of statements and theoretical discussions took us to the conclusion that leisure may be deemed as a strategy both to promote good health, as long as democratizing political actions are put in place and involve intersecting projects, and to incentive citizens to take part in political decision processes with use of incrementing educational programs for cultural entertainers who work with the issue of the community s right to have leisure. This way we expect that the associative lives of the community be leveraged through conceived claims based on planned, organized and regular interventions, which depend on a new civil protagonist that is at the same time political and critical, capable of breaking up the subordinate identity present in the lack of power of command and participation in the decision processes within the scope of the Brazilian social policy